Unidades bio habitacionales resiliencia Llanera (2021)
The project is to develop in the plains region more precisely in Tame - Arauca, an area that has been affected by the armed conflict in the last 40 years and as a result of this situation, its population has suffered the scourge of forced displacement from the rural area, limiting their right to enjoy a decent home, that is why the project “Bio-housing units resilience llanera” arises as an initiative to mitigate the damage; In this order of ideas, this housing project seeks not only to guarantee decent housing, but also from the architecture to give it an eco-sustainable approach with components derived from the rice husk and the “stem” or stem of the banana, products that abound in the region and in the case of bananas, it should be noted that Arauca is the number one department in the production of bananas nationwide with more than 793,084 tons per year, a product that is thrown away once the cut is made, that is why the Benefits for the region are incalculable, as it provides decent housing, generates employment and strengthens the economy of the region.